La mise au tombeau peinte par Antoine de Lonhy dans la cathédrale Saint-Jean-Baptiste à Saint-Jean-de-Maurienne - Séverine Haberer (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
« La mise au tombeau » (The Entombment) is one of the few known mural paintings by Antoine de Lonhy. It was created in the last quarter of the 15th century for one of the side chapels of the Jean-Baptiste cathedral. Between 2013 and 2014, it was restored and protected after salt marks appeared at the base of the painting, attacking the colored layer. This mural was discovered by chance in the 1960s, it had been moved at some stage, but never analyzed technically. The restoration work revealed that the artist used the technique of the applied brocades to paint fabrics, an exceptional technique for mural paintings.